An overview of the state of the regulatory and preclinical requirements for nanomaterials including medical devices. (20th May 2021) - Rehman, Naheed; Moore, Simon
Abstract: Nanomaterials when exposed to biological systems may produce oxidative stress, genotoxicity, and carcinogenicity, as nanoparticle toxicity is speculated to be different from larger particles of the same chemical composition due to the change of their physical properties from their smaller size and resultant higher surface area. Regulatory frameworks have become established to address the influx of nanomaterials to assess the potential benefit to human health but also where there is a risk to both human health and the environment. This article focuses on these regulatory frameworks, including the risk from inhalation, where these changes have already been implemented and reflected in the revised Organisation for Economic Co‐operation and Development OECD 412 and OECD 413 guidelines as additional investigations and endpoints have been added to determine the risk posed by this novel group of materials. Integr Environ Assess Manag 2021;17:1098–1104. © 2021 SETAC KEY POINTS: Nanomaterials are used in a broad range of applications, including their use in medicine as nanomedicines. Nanoparticle toxicity is speculated to be different from larger particles of the same chemical composition due to the change of their physical properties from their smaller size and resultant higher surface area. This article describes the evolution of global regulatory frameworks to assess the risk of nanomaterials to human health, focusing on the risk from inhalation, which has led to changes to OECD guideline studies to determine the risk of nanomaterials.